Facile Synthesis of 8-Hydroxymethyl-8,9-dihydro-2H-furo[2,3-h]chromene-3-carbaldehyde - Kumar, V.V.A.; Adiseshu, D.; Mohanraju, K. (Asian Journal of Chemistry, 2013)
7-Hydroxy-8-allyl-2H-3-chromene carbaldehyde and m-chloro benzoic acid in chloroform on heating to gave 8-hydroxymethyl-8,9-dihydro-2H-furo[2,3-h]chromene-3-carbaldehydes (3a-d) and 2H-3-chromene carbaldehyde reaction with malononitrile to gave 9-amino-6H-benzochromene-8,10-dicarbonitriles (6a-d) in good yields.